THE POTENTIAL OF CARDAMOM LEAF IN THE AGROFORESTRY SYSTEM: ESSENTIAL OIL YIELD AND 1.8-CINEOL CONTENT - Octavia, Dona; Wijayanto, Nurheni; Budi, Sri Wilarso; Batubara, Irmanida; Suharti, Sri (Association of Indonesian Forestry and Environment Researchers and Technicians, 2024)
Cardamom (Amomum cardamomum), the ‘Queen of spices’, is a native Indonesian spice, a type of potential biopharmaceutical currently prospective because of its high selling value, especially for its fruit, with various benefits and its wide use. So far, cardamom essential oil comes from the utilization of its fruit, but the production is more limited, unlike the sustainably produced leaves, therefore, its leaves have the potential to be developed. This study aims to analyze the essential oil yield and 1.8-cineol content of cardamom leaves essential oil (CLEO) grown in agroforestry systems. The CLEO was obtained by steam-water distillation, while the 1.8-cineol content was analyzed by gas chromatography–mass spectrometry (GC-MS). The experimental design employed was a Randomized Complete Block Design with three cropping patterns as a treatment and three doses of bokashi fertilizer as blocks. The results showed that the highest yield of CLEO was generated in the sengon + cardamom agroforestry pattern of 3.16%, and the highest content of 1,8-cineol in CLEO was generated in the sengon + cardamom + arrowroot agroforestry pattern of 47.23%, while the lowest yield of CLEO and the 1,8-cineol content were found in the monoculture pattern of 2,02% and 43.16% respectively. Agroforestry practices have the potential to increase 1,8-cineol content and the yield of essential oil in cardamom leaf, which will be prospective in forest management to support forestry multi-business and social forestry programs.